2012
DOI: 10.3758/s13421-012-0260-y
|View full text |Cite
|
Sign up to set email alerts
|

The reality of the past versus the ideality of the future: emotional valence and functional differences between past and future mental time travel

Abstract: Mental time travel (MTT) is the ability to mentally project oneself backwards or forwards in time in order to remember an event from one's personal past or imagine a possible event in one's personal future. Past and future MTT share many similarities and there is evidence to suggest that the two temporal directions rely on a shared neural network and similar cognitive structures. At the same time, one major difference between past and future MTT is that future as compared to past events generally are more emot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

44
166
8

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 143 publications
(218 citation statements)
references
References 74 publications
44
166
8
Order By: Relevance
“…This tendency to provide a greater number of emotionally positive personal events was particularly important for future events. These results are in agreement with the robust positivity bias and the 'rosy future effect' described in the literature dealing with AM and EFT Rasmussen and Bernsten 2013;Walker et al 2003). Equivalent performance were obtained for the post-scan questionnaire variables between the two groups (with the exception of the amount of details, showing a lower score for MS patients).…”
Section: Discussionsupporting
confidence: 79%
“…This tendency to provide a greater number of emotionally positive personal events was particularly important for future events. These results are in agreement with the robust positivity bias and the 'rosy future effect' described in the literature dealing with AM and EFT Rasmussen and Bernsten 2013;Walker et al 2003). Equivalent performance were obtained for the post-scan questionnaire variables between the two groups (with the exception of the amount of details, showing a lower score for MS patients).…”
Section: Discussionsupporting
confidence: 79%
“…2 D'Argembeau and Van der Linden (2004) manipulated the emotional valence and temporal distance of imagined events. It was found that participants reported greater autonoetic feelings and more vivid mental representations when imagining positive rather than negative, and temporally close rather than distant, future events (see also Berntsen & Bohn, 2010;Rasmussen & Berntsen, 2013). Szpunar and McDermott (2008) investigated the influence of the familiarity of contextual settings in which imagined future events take place.…”
Section: Introductionmentioning
confidence: 99%
“…et al, 2011), and it has been found that thoughts involving positive events have more social and self-regulating functions than thoughts involving negative events (Rasmussen & Berntsen, 2013). Drawing on the distinction between anticipatory and anticipated emotions as defined above, our aim here was to investigate whether valence effects in the perceived functions of prospections are similar for these two kinds of emotions.…”
mentioning
confidence: 99%
“…Compared with representations of negative future events, positive future events are more frequent and imagined faster (MacLeod & Byrne, 1996;Newby-Clark & Ross, 2003), are associated with more sensorial details, clearer representations of contextual information, greater feelings of pre-experiencing, and include more social contents (D'Argembeau & Van der Linden, 2004;de Vito, Neroni, Gamboz, Della Sala, & Brandimonte, 2014;Painter & Kring, in press;Rasmussen & Berntsen, 2013).…”
mentioning
confidence: 99%